Digital banking through a gender lens: examining trust and perceptions of Neobanks - Máté, Domicián; Alnouri, Bashir; Vveinhardt, Jolita (Business, Management and Economics Engineering, 2026)
Purpose – the aim of study is to examine how interface design elements (usability, presentation, navigation) influence trust, behavioural intention, and adoption of Neobanks among younger users, using data from students at the University of Debrecen, Hungary. Research methodology – a modified Technology Acceptance Model (mTAM) was tested via Partial Least Squares Structural Equation Modelling (PLS-SEM) using primary survey data (n = 159, valid respondents under 25 years old) and quasi-exploratory analysis from Neobank users. Findings – perceived ease of usage significantly mediates the relationship between interface quality and behavioural intention. Trust significantly impacts attitudes and intentions toward fintech, with stronger effects observed among female users. These insights advance cognitive trust theory in digital banking contexts. Research limitations – limited sample diversity and local scope at the University of Debrecen constrain generalizability. The PLS-SEM method focuses on prediction over theory testing may oversimplify complex trust dynamics. Future studies should employ mixed methods and cross-cultural samples for broader relevance. Practical implications – Neobanks can enhance adoption by prioritizing intuitive interface design and tailoring trust-building strategies to gender-specific user preferences. Originality/Value – this research integrates gender differences into mTAM and offers novel insights into trust formation for digital banking among younger European university students, A departure from prior studies is focused solely on technical features.